PENGARUH KEPEMIMPINAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BIRO ADMINISTRASI PEMBANGUNAN PENGADAAN BARANG DAN JASA PADA SEKRETARIAT DAERAH RIAU PEKANBARU - , Kurniawaty Fitri, Annisa Rahma Diani ,Jumiati Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of leadership, competence and work discipline on employee performance at the Development Administration Bureau, Procurement of Goods and Services, Regional Secretariat of Riau Province in Pekanbaru. This study took place at the Development Administration Bureau, Procurement of Goods and Services, Regional Secretariat of Riau Pekanbaru Province, with a total of 92 respondents. In this study consists of four variables. These variables are Leadership (X1), Competence (X2), Discipline (X3) and Employee Performance (Y). Methods of data analysis using Descriptive Analysis and Quantitative Analysis with Multiple Regression analysis tools, with the help of using a statistical application, namely SPSS version 23. The results of the study show that: 1) Leadership has a positive effect on employee performance. 2) Competence positively influences Employee Performance. 3) Work discipline has a positive effect on employee performance. 4) Leadership, competence and work discipline simultaneously affect employee performance. Keywords: Leadership, Competence, Work Discipline, Employee Performance